2020
DOI: 10.1002/ehf2.12938
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in heart failure care in a tax‐financed universal healthcare system: a nationwide population‐based cohort study

Abstract: Aims Data on socioeconomic-related differences in heart failure (HF) care are sparse. Inequality in care may potentially contribute to a poor clinical outcome. We examined socioeconomic-related differences in quality of HF care among patients with incident HF with reduced ejection fraction (EF) (HFrEF). Methods and results We conducted a nationwide population-based cohort study among patients with HFrEF (EF ≤40%) registered from January 2008 to October 2015 in the Danish Heart Failure Registry, a nationwide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This seems of particular relevance, as the study was conducted in the environment 29 where health indicators consistently show poorer levels of health and health-related behaviours and lower socio-economic standard, compared with other parts of Slovenia. 30 Other research 31,32 indicated particular challenges to self-care in such environments (i.e. limited economic resources, reduced use of HF care and lower levels of education).…”
Section: Discussionmentioning
confidence: 99%
“…This seems of particular relevance, as the study was conducted in the environment 29 where health indicators consistently show poorer levels of health and health-related behaviours and lower socio-economic standard, compared with other parts of Slovenia. 30 Other research 31,32 indicated particular challenges to self-care in such environments (i.e. limited economic resources, reduced use of HF care and lower levels of education).…”
Section: Discussionmentioning
confidence: 99%
“…Lower education has recently been associated with both higher morbidity 44 and inadequate health literacy 31 . Lower educational level and living alone, for example, have been associated with lower adherence to evidence‐based practice in heart failure care 45 . Regional differences in outcomes could indicate local differences in care provided.…”
Section: Discussionmentioning
confidence: 99%
“…31 Lower educational level and living alone, for example, have been associated with lower adherence to evidencebased practice in heart failure care. 45 Regional differences in outcomes could indicate local differences in care provided. This may translate into differences in access to vascular surgery 9 and underuse of evidence-based practices in wound care, which was seen in another study.…”
Section: Inequality In Healthmentioning
confidence: 99%
“…17 Tools for cardiac capacity stratification such as the New York Heart Association (NYHA) class, serve as a good prognostic factor in heart failure, lung disease, prescription pattern and quality of life. [18][19][20][21][22] Moreover, physicians' awareness of the number of drugs and benefit/risk profiles helps to prescribe fewer PIMs. 23 Presumably, CAD patients taking multiple medications, 24 or experiencing a high prevalence of frailty or transition to frail status, 25,26 are at the risks of receiving PIMs.…”
Section: Introductionmentioning
confidence: 99%